2008
DOI: 10.1159/000178815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intranasal Corticosteroids in the Treatment of Experimental Acute Bacterial Maxillary Sinusitis in Rabbits

Abstract: Objective: To investigate the possible effects of intranasal corticosteroids on the focal bacterial colonization and mucosal histomorphological changes in experimental acute bacterial maxillary sinusitis in rabbits. Methods: Acute bacterial maxillary sinusitis was induced in 48 rabbits. They were divided into 4 groups: antibiotic group (group A), antibiotic and corticosteroid combination group (group B), corticosteroid group (group C), and control group (group D). Six rabbits in each group were sacrificed to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…After the sponge removal on the 10th day, all animals had unilateral purulent rhinorrhea in the nasal cavity where they were inserted. This result is consistent with those of other studies 15 , 26 , 32 applying similar methods through the rhinogenic route, a model originally proposed by Marks, 20 using only the insertion of toxoid and/or buffer through the nasal cavity. Marks 20 had 83% success with this method; Liang et al 31 obtained 91.7% success in the induction of acute infection.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…After the sponge removal on the 10th day, all animals had unilateral purulent rhinorrhea in the nasal cavity where they were inserted. This result is consistent with those of other studies 15 , 26 , 32 applying similar methods through the rhinogenic route, a model originally proposed by Marks, 20 using only the insertion of toxoid and/or buffer through the nasal cavity. Marks 20 had 83% success with this method; Liang et al 31 obtained 91.7% success in the induction of acute infection.…”
Section: Discussionsupporting
confidence: 92%
“…Westrin et al 33 used this bacterium for the induction and observed its replacement after an average of five days. Cheng et al 26 did not isolate this agent in any rabbit 10 days after the start of induction. In the present study, S. pneumoniae was not identified in any of the assessed rabbits.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Experimental models allow assessments ranging from aspects related to the pathogenesis of rhinosinusitis to the effectiveness of different forms of treatment for this disease. 17 , 18 , 19 , 20 , 21 , 22 Among several methods described for rhinosinusitis induction, this study utilized the introduction of a sponge containing a toxoid agent into one of the nasal cavities of the animals. In addition to being a technically simple and efficient procedure to produce sinusitis in 100% of animals in several studies, 22 , 23 it causes little injury to the nasal mucosa and no sinus injury.…”
Section: Discussionmentioning
confidence: 99%